Leucocrit-The white face of acute myeloid leukemia - Tomas V Karajan (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2021)
Of a 72-year-old patient who was brought to our emergency room with fever and worsening condition for several weeks. Initial blood count showed a hemoglobin of 48g/L with a hematocrit of 0.14.